Tactile Textile - Shaikh, Sumayyah (School of Architecture, Planning and Geomatics, 2018)
The study is focused on the roles and principles of textiles, textile manipulation and its potential relationship with landscape architecture. Tactility bonds the two worlds of fashion and landscape together. It changes in scale, intimacy and movement. The study explores how textiles perform in relation to the following principles; movement, climate, reaction, light, transformation, scale and communication. The etymology of the word TEXTILE is derived from the Latin 'texre' meaning to weave or to construct. The word text is related to communication and the word 'tek' is related to building or architecture. The study has been conducted via various different media upon a range of different materials. These consist of film and media, light and shadow studies, projections, etching and transferring of textures, pattern cutting, stitching, and the making of paper and textile from plant material, to name a few. The act of textile manipulation and the product of these techniques is then used in the conventional site analysis that a landscape architect would conduct. These techniques being, a pleat, knot, veil, seam, weave, drape, dart and skirt. Each of these are broken down into their structural, functional and landscape roles. For example, a Veil is structurally light and semi opaque. Functionally it is aimed at concealing that which is behind it, yet it is not completely enclosed, thus revealing the object behind. In landscape design, a veil can be translated into a row or cluster of trees that is aimed at concealing objects in the background. Taking this process, a step further, these textile manipulation terms are then translated into verbs. These verbs of weaving, pleating, knotting etc. is then used as tools to analyze the site and its context in context of the act -of textile manipulation itself. From this, the area of study is broken up into pattern pieces. This unlocks a new perspective on how each of these pieces' work -or do not work- together. This then begin to set out a set of opportunities and constraints for the site and its surroundings. Are there potential seams or connections that have not yet been realized? Are there opportunities in the converging topographic darts?. As previously mentioned many of the design principles and ideas we know in architecture have been influenced and have influenced textiles and fashion. This study is focused on the act of textile manipulation and the properties of different materials.